Colonial heterotopia as metanarrative in white rhodesian writing: a post-millennial reading of Peter Godwin’s Mukiwa: a white boy in Africa. - Javangwe, Tasiyana D. (Unisa Press, 2021)
The concept of space, both as metaphor and metonym, is critical to the understanding of the politics of identity construction and expression in white Rhodesian writing. The presence of conceived white spaces and symbols continue to be valorised and celebrated in white Rhodesian writings despite the new political dispensation ushered in 1980, suggesting a deep-seated imagination that continues to inform and nourish white colonial identities. Such imaginations of space can, it will be argued in this article, be interpreted as metanarratives that strive towards self-preservation strategies of white identity and discursive privilege. Foucault’s concept of heterotopia is used in this discussion as a suitable conceptual framework both to apprehend and destabilise Rhodesian imaginations of privileged spaces in the post-millennial era.